Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/tropicalmed5040178
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequency of Blastocystis Subtypes 1, 2, and 3 in Urban and Periurban Human Populations of Arequipa, Peru

Abstract: Blastocystis is one of the most common protozoa found in the human gut and are genetically diverse and widely distributed around the world. Nonspecific and inconsistent symptoms have been associated with this protozoon; thus, its clinical importance remains controversial. Our aim was to estimate the relative frequency of Blastocystis subtypes 1, 2, and 3, which are the predominant subtypes reported in South America, based on conserved regions of SSU rDNA sequences and determine the factors associated with them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…This study showed that ST3 was the predominant subtype in boys and girls, followed by ST1 and ST2. This result was similar to that of previous studies in Thailand [35,36] and others in different countries, such as Malaysia [37], Turkey [38], Peru [39], and Italy [40]. Our finding showed 18S alleles of Blastocystis in each ST, which include allele 4 (ST1), allele 9 (ST2), and alleles 34 and 37 (ST3).…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that ST3 was the predominant subtype in boys and girls, followed by ST1 and ST2. This result was similar to that of previous studies in Thailand [35,36] and others in different countries, such as Malaysia [37], Turkey [38], Peru [39], and Italy [40]. Our finding showed 18S alleles of Blastocystis in each ST, which include allele 4 (ST1), allele 9 (ST2), and alleles 34 and 37 (ST3).…”
Section: Discussionsupporting
confidence: 92%
“…However, studies in South America about Blastocystis specifically in animals are scarce. In some South American countries, there are studies reporting different Blastocystis STs in humans and their relationship with symptomatic patients (54)(55)(56)(57)(58). Countries from the Americas where animal samples have been tested from Blastocystis include United States (16,23,29,59), Brazil (25), Mexico (31), Ecuador (35), Peru (34) and Colombia (26).…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the metabarcoding data used in the present study had been generated for various independent research projects and routine diagnostic purposes and were recently used in a separate study (Stensvold et al, 2022). Data representing fecal samples collected in Peru and Tunisia (Ascuna-Durand et al, 2020;Chihi et al, 2019Chihi et al, , 2022 were added. Thus, the 1457 fecal DNA datasets represented populations sampled in Algeria, Denmark, Egypt, Peru, Tunisia, Turkey, and United Kingdom, with and without gastrointestinal symptoms.…”
Section: At Er I a L S A N D M Et Hod S Datamentioning
confidence: 99%